Daily Clinical Practice in the Management of Chronic Urticaria in Spain: Results of the UCREX Study - M. Ferrer Puga; J.F. Silvestre Salvador; J. Bartra Tomas; A. Giménez-Arnau; M. Labrador-Horrillo; J. Miquel-Miquel; F.J. Ortiz de Frutos; J. Sastre Dominguez; A. Valero Santiago; P. Terradas-Montana; M. Vidal-Jorge; I. Jáuregui Presa (Elsevier, 2022)
Background: Chronic Urticaria (CU) is a debilitating disease whose treatment is mainly symptomatic. UCREX study aimed to identify CU patients' profile, disease management and quality-of-life (QoL) in daily clinical practice in Spain. Methods: Observational, 12-months prospective, multicenter study, included de novo or established CU patients attending to dermatology/allergy consultations in 39 Spanish hospitals. Main variables: Urticaria Activity Score (UAS), UAS over 7 days (UAS7). Secondary variables: CU-QoL Questionnaire (CU-Q2oL), EuroQol-5 dimensions (EQ-5D), Medical Outcomes Study Sleep (MOS-Sleep) scale, Hospital Anxiety and Depression Scale (HADS). Results: 361 patients included. Of them, 176 (48.8%) considered for the main objective analysis. Mean age (SD) of 46.6 (14.2) years and 71.8% women. The year prior to inclusion, most patients (57.1%) were treated with non-sedating H1-antihistamines (NS-H1AH). At baseline, mean (SD) 3.6 (6.8) visits were registered to primary care. Mean (SD) UAS7 at baseline was 14.3 (11.0) and CU-Q2oL 24.1 (17.0) which tended to improve by 8.6 (9.7) and 13.9 (15.0), respectively, at 12-months. MOS-Sleep and EQ-5D remained steady during the study, except pain/discomfort and anxiety/depression which went from 58.7% and 49.6% to 29.6% and 26.9%, respectively. At baseline, HADS showed a mean (SD) anxiety of 8.7 (4.5) and depression 5.1 (4.4), decreasing to 7.0 (4.3) and 4.7 (4.3), respectively, at 12-months. Conclusions: Although most CU patients are treated with NS-H1AH, disease activity is still important, negatively affecting patients' QoL, work activity and healthcare resources use. An appropriate disease management could be the basis for symptoms control, QoL improvement and resources optimization. Resumen: Antecedentes: La urticaria crónica (UC) es una enfermedad debilitante cuyo tratamiento es principalmente sintomático. El estudio UCREX tuvo como objetivo identificar el perfil de los pacientes con UC, el manejo de la enfermedad y la calidad de vida (CdV) en la práctica clínica diaria en España. Métodos: Estudio observacional, prospectivo, multicéntrico de 12 meses, que incluyó pacientes con UC de novo o establecida que acudieron a la consulta de dermatología/alergología de 39 hospitales españoles. Las variables principales fueron: el Urticaria Activity Score (UAS) y el UAS por siete días (UAS7). Las variables secundarias fueron: el cuestionario de CdV de urticaria crónica (CU-Q2oL), el EuroQol-5 Dimensiones (EQ-5D), la escala Medical Outcomes Study Sleep (MOS-Sleep) y la escala hospitalaria de ansiedad y depresión (HADS). Resultados: Se incluyeron 361 pacientes, de los cuales 176 (48,8%) formaron parte del análisis del objetivo principal. La edad media (DE) fue de 46,6 (14,2) años y el 71,8% eran del sexo femenino. El año anterior al periodo de inclusión de los pacientes, la mayoría de ellos (57,1%) se habían tratado con antihistamínicos H1 no sedantes (AHNS-H1). En la basal, se registró una media (DE) de 3,6 (6,8) de visitas a atención primaria. La media (DE) del UAS7 en la basal fue de 14,3 (11,0) y del CU-Q2oL 24,1 (17,0), observándose una tendencia en la mejoría en 8,6 (9,7) y 13,9 (15,0), respectivamente, a los 12 meses. El MOS-Sleep y el EQ-5D se mantuvieron estables durante el estudio, excepto por el dolor/malestar y la ansiedad/depresión que pasaron de 58,7 y 49,6% a 29,6 y 26,9%, respectivamente. En situación basal, el HADS mostró una ansiedad media (DE) de 8,7 (4,5) y una depresión de 5,1 (4,4), disminuyendo respectivamente a 7,0 (4,3) y 4,7 (4,3) a los 12 meses. Conclusiones: Aunque la mayoría de los pacientes son tratados con AHNS-H1, la actividad de la enfermedad sigue siendo importante, afectando negativamente a su CdV, su actividad laboral y repercutiendo negativamente en el uso de recursos sanitarios. Un manejo adecuado de la enfermedad podría ser la base para alcanzar el control de los síntomas, la mejora de la CdV y la optimización de los recursos sanitarios necesarios.